2017
DOI: 10.1002/2016wr019254
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic and spatial‐temporal dynamic slope effects on soil erosion during rainfall‐runoff processes

Abstract: The slope effect on flow erosivity and soil erosion still remains a controversial issue. This theoretical framework explained and quantified the direct slope effect by coupling the modified Green‐Ampt equation accounting for slope effect on infiltration, 1‐D kinematic wave overland flow routing model, and WEPP soil erosion model. The flow velocity, runoff rate, shear stress, interrill, and rill erosion were calculated on 0°–60° isotropic slopes with equal horizontal projective length. The results show that, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 85 publications
4
20
0
Order By: Relevance
“…The rill erosion process by rill flow consists of the following processes: rill flow, rill erosion, and sediment transport. The 1‐D diffusive wave equation is applied to describe the rill flow process and a similar form was utilized by WEPP (Flanagan & Nearing, ), Liu et al (), Tayfur (), An and Liu (), and Wu et al (). It should be noted that, in the present model, the total width of the representative rills is considered to vary along the hillslope and the length and slope gradient of the representative rills vary accordingly in each longitudinal interval.…”
Section: Modeling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The rill erosion process by rill flow consists of the following processes: rill flow, rill erosion, and sediment transport. The 1‐D diffusive wave equation is applied to describe the rill flow process and a similar form was utilized by WEPP (Flanagan & Nearing, ), Liu et al (), Tayfur (), An and Liu (), and Wu et al (). It should be noted that, in the present model, the total width of the representative rills is considered to vary along the hillslope and the length and slope gradient of the representative rills vary accordingly in each longitudinal interval.…”
Section: Modeling Approachmentioning
confidence: 99%
“…As an essential element of hillslope geomorphology, the characteristics of rill network planform, particularly the local number of rills (the number of rills at a certain cross section, representing the local rill density) and rill orientation angle (an average angle between directions of a rill at measurement points and the vertical direction of the rill), have remarkable impacts on flow and sediment routing from the interrill areas to the rills and on the local rill length, width, and slope gradient (Oz et al, ; Shen et al, ). However, most previous studies only account for the effects of rainfall intensity, soil characteristics, slope length, steepness, vegetation, and soil sealing (Assouline & Ben‐Hur, ; Chen et al, ; Huang, ; Jomaa et al, ; Jouquet et al, ; Robichaud et al, ; Tromp‐van Meerveld et al, ; Wu et al, ; X. Zhang et al, ) and largely ignore the impacts of rill network planform, especially in modeling studies. Therefore, introducing the impacts of rill planar characteristics into hillslope runoff and soil erosion models has the potential to improve runoff and soil erosion predictions on a rilled hillslope.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen in Figure 10 that cumulative infiltration difference between 15 • and 20 • slopes was mainly lay in area 10-50 m and 150-200 m from the slope top. Wu et al [37] also found the critical slope for runoff rate was around 11 • regardless of rainfall duration and slope length through a modified Green-Ampt model. The critical slope of total runoff may be affected by the surface condition (e.g., vegetation coverage, surface roughness) and the soil property (e.g., permeability, soil surface sealing), which worth further investigation.…”
Section: The Impact Of Slope Gradient On Total Runoff and Erosion Undmentioning
confidence: 91%
“…The retention of water input (rainfall) is influenced by soil moisture storage, which impacts the runoff generation mechanism (Geroy et al, 2011). The overland flow resulting from rainfall causes soil erosion (Holz, Williard, Edwards, & Schoonover, 2015;Vaezi, Ahmadi, & Cerdà, 2017), which may vary according to the slope (Wu, Yu, & Chen, 2017), vegetation, and soil condition. So, it is indispensable to study the mechanism of overland flow in different land conditions, which is possible through plot-scale studies.…”
Section: Introductionmentioning
confidence: 99%